2007
DOI: 10.1167/iovs.06-0145
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Retinal Toxicity of Intravitreal Commercially Available Preserved Triamcinolone Acetonide (Kenalog) in Rabbit Eyes

Abstract: No demonstrable electroretinographic or histologic changes occurred to suggest immediate or delayed widespread retinal toxicity of IVTK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 18 publications
(34 reference statements)
0
29
0
3
Order By: Relevance
“…Most animal studies did not show significant intraocular toxicity [5,231,232,233,234,235]. As early as 1981, McCuen et al [5] performed intravitreal injections of 1 mg of TA into 1 eye of each of 21 rabbits, whereas the other eye received an injection of an equal volume of saline solution as a control.…”
Section: Preclinical (Animal) Studiesmentioning
confidence: 99%
“…Most animal studies did not show significant intraocular toxicity [5,231,232,233,234,235]. As early as 1981, McCuen et al [5] performed intravitreal injections of 1 mg of TA into 1 eye of each of 21 rabbits, whereas the other eye received an injection of an equal volume of saline solution as a control.…”
Section: Preclinical (Animal) Studiesmentioning
confidence: 99%
“…In recent years, TA is used with intravitreal or trans-tenon's retrobulber infusion also for the treatment of macular edema [17][18][19][20][21], AMD with [22][23][24] or without [25] photodynamic therapy, serous macular detachment in central retinal vein occlusion, [26] in a combination with vitrectomy [27,28], or with anti-vascular endothelial growth factor treatment for AMD [29]. The efficacy of TA has been well proven from the enormous clinical data, though its side effects [30][31][32] and the reports about its toxicity [33][34][35][36] are to be argued. However, the effects of TA during the healing process and its role in treatment remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition it has been demonstrated that periocular corticosteroids can reduce the severity of experimental PVR [Rubsamen and Cousins, 1997]. Laboratory work has also demonstrated that triamcinolone appears to have no significant retinal toxicity [Albini et al, 2007] although in vitro it may be toxic to proliferating retinal cells [Narayanan et al, 2006]. Clinically intravitreal triamcinolone has recently been extensively used to treat macular oedema, intraocular inflammation and subretinal neovascularisation without demonstrable retinal toxicity but with a notable incidence of raised intraocular pressure and cataract [reviewed by Pathamanthan and Reck, 2006].…”
Section: Heinrich Heimannmentioning
confidence: 99%